Ethanol extract of Dalbergia odorifera protects skin keratinocytes against ultraviolet B-induced photoaging by suppressing production of reactive oxygen species. Issue 5 (4th May 2015) - Ham, Sun Ah; Hwang, Jung Seok; Kang, Eun Sil; Yoo, Taesik; Lim, Hyun Ho; Lee, Won Jin; Paek, Kyung Shin; Seo, Han Geuk
Graphical abstract: : D. odorifera extract protects skin keratinocytes against UVB-induced photoaging by suppressing production of ROS and expression of p53 and p21. Abstract: Dalbergia odorifera T. Chen (Leguminosae), an indigenous medicinal herb, has been widely used in northern and eastern Asia to treat diverse diseases. Here, we investigated the anti-senescent effects of ethanolic extracts of Dalbergia odorifera (EEDO) in ultraviolet (UV) B-irradiated skin cells. EEDO significantly inhibited UVB-induced senescence of human keratinocytes in a concentration-dependent manner, concomitant with inhibition of reactive oxygen species (ROS) generation. UVB-induced increases in the levels of p53 and p21, biomarkers of cellular senescence, were almost completely abolished in the presence of EEDO. Sativanone, a major constituent of EEDO, also attenuated UVB-induced senescence and ROS generation in keratinocytes, indicating that sativanone is an indexing (marker) molecule for the anti-senescence properties of EEDO. Finally, treatment of EEDO to mice exposed to UVB significantly reduced ROS levels and the number of senescent cells in the skin. Thus, EEDO confers resistance to UVB-induced cellular senescence by inhibiting ROS generation in skin cells.